Sexual Issues: The Analysis of Female Role Portrayal Preferences in Taiwanese Print Ads - Lin, Chyong-Ling (Journal of business ethics, 2008)
For a long time, female endorsers in advertising have been doing product information promotion in the market. However, with more and more highly educated women participating in the labor force, the conception of feminist depictions in advertising have become a perplexing issue. The traditional female role portrayals or stereotypes of the past are not able to totally reflect the expectations, behavior, attitudes, and beliefs of contemporary women. The author collected print ads as data from three types of the highest circulation magazines: foreign women’s magazines (Chinese edition), domestic women’s magazines, and domestic management magazines subscribed to in Taiwan to investigate what were the favorite feminine patterns and feminist depictions in a traditionally masculine society. The results showed classical beauty and girl-next-door images were “acceptable” gender-role behavior exposed highly in domestic magazines, which might contribute to conservative Confucian beliefs. On the other hand, being trendy was a significantly high preference for contemporary feminist depictions in foreign women's magazines; it might be considered as being due to the increased educational level of women and female labor participation rate in the work place as well as upgrading of social status.